2010
DOI: 10.2202/1556-3758.1623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drying Parameters on the Drying Kinetics of Fermented Ground Cassava Using a Rotary Dryer

Abstract: The effects of drying parameters on the drying kinetics of fermented ground cassava were studied. Fermented ground cassava (TMS 30572) was dried in a bench scale rotary dryer at different inlet air temperature (115-230°C), inlet air velocity (0.83-1.55 m/s), feed drive speed (12-100 rpm), drum drive speed (8-18 rpm), relative humidity of inlet air (50 to 80 percent), and mass of feed (50-500 g). It is shown that inlet air temperature and inlet air velocity have the most significant effects on the drying rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was shown that the inlet air temperature and velocity had the most significant effects on the drying rate of cassava. A model that predicted the drying rate as a function of the two significant parameters above was presented and the accuracy of the prediction model was verified by comparison with experimental results (Taiwo, Abowei, Puyate, & Achinewhu, 2010). Sai carried out many rotating drying experiments under different operating conditions, which indicated that increasing the temperature or flow rate of hot air at the inlet or the rotational speed of the rotary dryer increased the drying rate of the material and an increase in the mean residence time reduced the average final moisture content of the material (Sai, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…It was shown that the inlet air temperature and velocity had the most significant effects on the drying rate of cassava. A model that predicted the drying rate as a function of the two significant parameters above was presented and the accuracy of the prediction model was verified by comparison with experimental results (Taiwo, Abowei, Puyate, & Achinewhu, 2010). Sai carried out many rotating drying experiments under different operating conditions, which indicated that increasing the temperature or flow rate of hot air at the inlet or the rotational speed of the rotary dryer increased the drying rate of the material and an increase in the mean residence time reduced the average final moisture content of the material (Sai, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Compared to modern electronic relative humidity sensors such as capacitive relative humidity sensors or resistive relative humidity sensors, the psychrometer is one of the relative humidity measurement devices that can be used in a dirty environment, can withstand state changes of water, and can provide a large range of measurement values. The psychrometer is used in different measurement environment in many current applications [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%